Gameful Design of an Application for Patients in Rehabilitation - Menychtas, Andreas; Galliakis, Michael; Pardos, Antonis; Panagopoulos, Christos; Karpouzis, Kostas; Maglogiannis, Ilias (Frontiers in Computer Science, 2022)
The design process of any interactive application is an important part of its lifecycle, since it largely defines its structure, means of interaction with the users and its actual content. In the case of applications related to medical uses and self-help, it is even more important, given the aims of the application, the diversity of target users and the urgent need for increased retention. In this paper, we present a gameful design process for a mobile application targeted towards patients in rehabilitation, implementing concepts related to increasing user rapport and motivation through gamification, and means to offer guidance and personalised services to improve user experience. Both gamification and personalisation build on narrative concepts, by putting patients in the place of a "hero", offering them the opportunity to overcome "challenges" and receive a clear view of their progress (a.k.a. a "hero's journey"), both in terms of physical and mental condition. Finally, we discuss measurable indicators used to evaluate the application in terms of the progress that patients showed, their motivation and interest, and degree of adherence to the exercise plans.